ANALISIS MANAJEMEN RISIKO PADA ORGANISASI IKATAN MAHASISWA MUHAMMADIYAH MENGGUNAKAN METODE ANALISIS RISIKO ISO 31000 - Riza, Aninda Celina Alya; Azzahra, Alda Yasfa; Rochman, Candra Bagus Ainur; Zakariya, Novie Andriani; Aninda Celina Alya Riza; Alda Yasfa Azzahra; Candra Bagus Ainur Rochman; Novie Andriani Zakariya (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2024)
The Muhammadiyah Student Association (IMM) at the State Islamic University of Sunan Ampel Surabaya (UINSA) was established in 1989 and expanded from three to five branches in 1992 following the merger of several faculties. Despite this growth, IMM often faces organizational challenges, including issues related to communication, collaboration, and financial dependency. This study aims to explore the application of ISO 31000-based risk management at IMM UINSA. The primary goal is to understand the obstacles, challenges, and opportunities for improvement in risk management within this organization to enhance its sustainability and success in the future. The research adopts a qualitative approach, utilizing in-depth interviews and participatory observation methods. Interviews were conducted with IMM members and leaders to identify the main risks faced, while participatory observation was used to evaluate the application of ISO 31000-based risk management principles. The findings of the study identify three main risks: low communication effectiveness leading to misunderstandings and conflicts among members, emotional challenges that hinder collaboration and team spirit, and financial dependency on Muhammadiyah, which could lead to financial instability. To address these risks, proactive and adaptive risk management strategies are recommended, including strengthening communication, team-building activities, and diversifying funding sources. With these insights and strategies, IMM can enhance the organization's sustainability and success in the future.